An analysis of the effects of time budget pressures towards the quality of audited financial statements - Gangata, Gladys Ruvarashe (Midlands State University, 2018)
This research on the effects of time budget pressure on the quality of the audited financial statements focusing on the deliberate practice of dysfunctional behaviour by auditors. The objective of this research was to establish the effect of time budget pressure on audit quality and auditors’ behaviour, cause of dysfunctional behaviour, how it contributes to audit risk, thereby ultimately affecting audit quality and provide best practices that can be adopted to reduce time budget pressure and maintain quality in audits. Qualitative research method and a descriptive research design were utilised. . The target population was Deloitte Zimbabwe Audit Staff which was selected utilising random stratification. The target population was 85 from which a sample of 60 participants was selected. The research used questionnaires, interviews to gather evidence. The findings were that the firms are most busy during the first quarter of the year which inflicts time budget pressure on auditors. Time budget pressure significantly affects auditors’ behavior therefore it is a major cause of dysfunctional behaviour. Auditors practice dysfunctional as a way of coping with the pressure. Results also show that time budget pressure affects detection of risk but also affect audit risk but to a lesser extent because there is inherent risk and control risk which also affect AQ. The recommendation were that firm may make consultation with the junior staff before setting of time budgets, encourage staff to record the actual time worked without penalizing for underperforming. Firm should emphasize the importance of performing high audit quality and conduct more and better training.